Masters of violence : the plantation overseers of eighteenth-century Virginia, South Carolina, and Georgia - Stubbs, Tristan (Carolina lowcountry and the Atlantic world., 2018)
"The overseer performed a role of singular importance to the plantation economies of the eighteenth-century South. Ultimately the responsibility for a profitable return on his employer's investment in land and human property fell to him, ahead of the estate steward or planter's agent, both of whom were superior in the management hierarchy. Stubbs's book contends that eighteenth-century overseeing is integral to understanding the development of slaveholder paternalism in the nineteenth century"--